EVALUATION OF PATIENT SAFETY STEPS IN GENERAL HOSPITAL OF YOGYAKARTA CITY (RSUD YOGYAKARTA CITY) - Wilda Apriyani; Liena Sofiana (International Journal of Healthcare Research, 2018)
Background of Study: Patient Safety of hospital is a system where the hospital makes patient adoption safer. In giving a quality of guarantee provide health and patient safety, this hospital is applying patient safety program. The result of our acknowledgements show SOP that has not been working as accurately. At this incident should be told 2x24 hours maximal, sometime there is exceeding the line and it is not reported. The purpose of this project is to evaluate the step of patient's safety that has been applied at the inpatient installation in the regional hospital of Yogyakarta.Research Method : this research is a qualitative research with case approach to 6 informan that used an interview guidance and check list which is refering to the minister of health on Patient’s Safety. Analysis data used data reduction, data display and conclusion.The results of study: the result of this research showed six of seven steps of patient safety has been working with the rule of minister of health about of patient safety, althought in progressing need an increasing . However, your leaders and proponents has not been working with the rule of minister of health about of patient safety.Conclusion : this research is one of seven steps of patient safety, 6 steps has been working with the rule of minister of health about of patient safety.